Investigating the EEG profile of elite and non-elite players in the basketball free throw task - Keshvari, F.; Farsi, A.; Abdoli, B. (Journal of Motor Behavior, 2024)
This study aimed to investigate the electroencephalographic profile of elite and non-elite basketball players seconds before and during the basketball free throw. Sixteen male subjects in the elite group (national team/premier league players with an average age of 22.06 ± 1.56) and 16 male non-elite subjects (university players with an average age of 22.37 ± 1.45) voluntarily participated in this research. Electroencephalographic data were measured from 28 cortical areas using a mobile wireless device. ANOVA with repeated measures were also performed to investigate the characteristics of theta, alpha, and beta frequency bands. The findings showed the higher cortical activity of the elite group. Different frequency bands exhibited similar asymmetry patterns, suggesting the higher activity of the left hemisphere in most of the homologous sites. Moreover, the activity of frequency bands in the left hemisphere rose by approaching the moment of throw. Furthermore, the activity of a limited number of right hemisphere sites increased by getting closer to the moment of action. In general, hemispheric asymmetry in favor of the left hemisphere has a cortical pattern, reflecting high-performance activities. In addition, the characteristics of different frequency bands of hemispheres are directed toward increasing cognitive processing, attention focusing, and inhibiting irrelevant information.